(untitled) (Международный научный журнал «Инженер», 2026)
In this article, in order to create good conditions for the population in Uzbekistan, including the need for drinking water: population growth, urbanization, climate change, and other problems, experimental work was carried out on local sand, including black sand. It was stated that this sand filtration device can retain unnecessary substances in water that are harmful to human health and make water reusable. Methodologically, an attempt was made to achieve a new approach to the problem based on literature analysis, practical analysis, and the formula for the dependence of filtration speed on hydraulic gradient developed by Darcy. Water that leaked from black sand was analyzed using a TDS&EC tester and a spectrophotometer. These analyses are presented in tables and diagrams.